Improvement of Channel Mobility of GaN‐MOSFETs With Thermal Treatment for Recess Surface. Issue 10 (19th December 2017) - Uesugi, Kenjiro; Shindome, Aya; Kajiwara, Yosuke; Yonehara, Toshiya; Kato, Daimotsu; Hikosaka, Toshiki; Kuraguchi, Masahiko; Nunoue, Shinya
Abstract : In this work, a thermal treatment technique under NH3 ambient for the recess surface of GaN‐MOSFETs is developed. Immediately following the fabrication process of the recess, the bottoms of these structures have rough surfaces and step‐terrace structures cannot be observed because of the plasma‐induced damage. However, clear step‐terrace structures are formed by the thermal treatment, and the RMS values of the surface roughness decrease from 0.26 to 0.14 nm, which is comparable to those of the as‐grown epitaxial film. In addition, it is confirmed that concentrations of impurity atoms introduced during the recess fabrication process are decreased by the thermal treatment. The channel mobility of the GaN‐MOSFETs without the thermal treatment is 118 cm 2  Vs −1, whereas that of the device whose fabrication process includes the thermal treatment increased to 149 cm 2  Vs −1 . These results indicate that the thermal treatment under NH3 ambient is effective for reducing on‐state resistance of GaN‐MOSFETs. Abstract : In this paper, thermal treatment technique under NH3 ambient for the recess surface of GaN‐MOSFETs in order to remove plasma‐induced damage is demonstrated. Atomically flat interface between SiO2 and GaN at the recessed‐gate and improved channel mobility of the MOSFETs are achieved utilizing the thermal treatment under appropriate temperature and NH3 partial pressure.